Tunable anion transport and the chemical transistor effect in functionalized graphene oxide membranes - Siyu Chen; Gladys Shi Xuan Tan; Artemii Ivanov; Timofey M. Savilov; Kou Yang; Xuanye Leng; Musen Chen; Kostya S. Novoselov; Daria V. Andreeva (npj 2D Materials and Applications)
Abstract Selective anion transport is essential for energy conversion, water purification, and electrochemical systems, yet achieving precise ion selectivity in membranes remains a challenge. Here, we present an amino-functionalized graphene oxide (am-GO) membrane that enables tunable anion transport through nanochannels. Using a combined experimental and computational approach, we consider the three stages of ionic transport—absorption, diffusion, and desorption—to reveal that Cl− selectively diffuses through nanochannels, while NO3 −, SO4 2−, and PO4 3− are excluded. In ionic mixtures, the chemical transistor effect emerges, where Cl− pulls water from NO3 − hydration shell, enhancing its mobility, while SO4 2− and PO4 3− remain excluded due to size constraints. This mechanism enables precisely regulated Cl− and NO3 − transport, with ultrahigh rejection rates of 99.99% for SO4 2− and PO4 3−, even in complex ionic environments. The am-GO exhibits stability and anion-hopping mechanisms, making it a versatile platform for anion exchange membranes in electrolysis, energy storage, and environmental applications.